Re-irradiation with protons or heavy ions with focus on head and neck, skull base and brain malignancies - Seidensaal, Katharina; Harrabi, Semi B.; Uhl, Matthias; Debus, Jürgen (BJR case reports, 2020)
Re-irradiation can offer a potentially curative solution in case of progression after initial therapy; however, a second course of radiotherapy can be associated with an increased risk of severe side-effects. Particle therapy with protons and especially carbon ions spares surrounding tissue better than most photon techniques, thus it is of high potential for re-irradiation. Irradiation of tumors of the brain, head and neck and skull base involves several delicate risk organs, e.g. optic system, brainstem, salivary gland or swallowing muscles. Adequate local control rates with tolerable side-effects have been described for several tumors of these locations as meningioma, adenoid cystic carcinoma, chordoma or chondrosarcoma and head and neck tumors. High life time doses nonetheless lead to a different scope of side-effects, e.g. an enhanced rate of carotid blow outs has been reported. This review summarizes the current data on particle irradiation of the aforementioned locations and malignancies.